2015
DOI: 10.2503/hortj.mi-002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bacillus velezensis</i> and <i>Glomus intraradices</i> on Fruit Quality and Growth Parameters in Strawberry Soilless Growing System

Abstract: This study evaluates the effect on the 'Splendor' and 'Primoris' strawberry cultivars of different dates of inoculation with Glomus intraradices, an arbuscular mycorrhizal (AM) fungus. Additionally, plants were grown in a soilless growing system with or without Bacillus velezensis at the beginning of the experiment. A completely randomized block design (2 biofertilizer treatments × 2 cultivars × 3 inoculation dates) with 2 replications was used. Each replicate consisted of one bag with 10 plants. Fruit weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…A positive effect of the use of preparations containing bacteria (Bacillus subtilis GBO3 and B. amyloliquefaciens IN937a) on the yield and quality of strawberry fruit was found by Kokalis-Burelle (2003). As reported by Palencia et al (2015), the effect of mycorrhizal and bacterial preparations on the weight of strawberry fruit depended on many factors, including the variety being cultivated and the time of inoculation. In the opinion of those authors, the largest increase in fruit weight was obtained following the use of bacteria and fungi (Bacillus velezensis and Rhizophagus intraradices) at the beginning of the strawberry growing cycle.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A positive effect of the use of preparations containing bacteria (Bacillus subtilis GBO3 and B. amyloliquefaciens IN937a) on the yield and quality of strawberry fruit was found by Kokalis-Burelle (2003). As reported by Palencia et al (2015), the effect of mycorrhizal and bacterial preparations on the weight of strawberry fruit depended on many factors, including the variety being cultivated and the time of inoculation. In the opinion of those authors, the largest increase in fruit weight was obtained following the use of bacteria and fungi (Bacillus velezensis and Rhizophagus intraradices) at the beginning of the strawberry growing cycle.…”
Section: Discussionmentioning
confidence: 84%
“…Increased colonization of plant roots by AM fungi is often observed in plants under abiotic stress conditions, e.g., drought (Boyer et al 2015;Moradtalab et al 2019), so the near-optimal growing conditions of our study could have been the cause of the low mycorrhizal frequency in the roots of our strawberry plants. Numerous studies confirm the beneficial effect of AMF inoculation on plant growth (Palencia et al 2015;Sas-Paszt et al 2011Derkowska et al 2015a). Boyer et al (2015) had found that the inoculation of strawberry plants with two species of arbuscular mycorrhizal fungi (Funneliformis mosseae BEG25, F. geosporus BEG11) had a positive effect on plant growth and on increasing the population of AMF in the roots, in comparison with plants without mycorrhizas.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Over the last 5 years (2012–2016), strawberry ( Fragaria × ananassa Duch) production in Portugal has almost tripled (3091 t in 2012 and 10 753 t in 2016), partly due to affordability, as well as the fruit's beneficial effects on health. Strawberries are prized by consumers not only for their organoleptic properties but also their low water content and high mineral and vitamin levels, easily meeting basic nutritional requirements . Nevertheless, the main interest in the fruit is its antioxidant potential, giving it important health‐promoting activity.…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry cropping requires extensive use of fertilizers at various stages during the plant life cycle, which are expensive and pose environmental hazards . The use of PGPB in strawberry cropping can have important environmental benefits, as it may help to reduce the use of chemical fertilizers, decrease fertilizer costs and suppress phytopathogens, and may help to sustain soil productivity . Recent studies have confirmed that the use of biofertilizers containing several strains of the genus Bacillus is beneficial for plant growth, yield and fruit quality of strawberries .…”
Section: Introductionmentioning
confidence: 99%